Identification of environmentally friendly of technology fishing gears in Bireuen District - Rizka Maula; Makwiyah A. Chaliluddin; Ichsan Setiawan; Indra Indra; Muhammad Rusdi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Bireuen District has significant potential in fisheries resources. However, the high potential of marine fisheries comes with various threats, such as overfishing and destructive fishing, which can disrupt the sustainability of marine ecosystems. The use of environmentally friendly fishing gear is a crucial aspect of sustainability. This study aims to identify environmentally friendly fishing technologies in Bireuen District. Data collection was conducted using a descriptive method with survey techniques, observations, and structured interviews with respondents. The sampling method employed purposive sampling, selecting respondents based on specific criteria or considerations relevant to the research objectives, with a total of 50 respondents directly involved in capture fisheries in Bireuen District. Data analysis was carried out using a scoring analysis based on nine criteria for environmentally friendly fishing gear, following the guidelines of the Code of Conduct for Responsible Fisheries.The results of the study indicate that fishing gears with very environmentally friendly technology include purse seines, trolling lines, set longlines, pots, and gillnets. Meanwhile, beach seines and trammel nets are categorized as less environmentally friendly.Keywords:Fishing gearEnvironmentally FriendlyCapture fisheriesCCRFBireuen District